The Islamic Legal Analysis of Mixed Rice Buying and Selling Transactions in Traditional Markets - Jasri, Jasri; Aidil, Andi Muhammad; S, Abdillah; Mustaming, Mazlizah (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2023)
The transaction of buying and selling according to the perspective of fiqh constitutes a contractual agreement regarding a specific item, wherein the seller explicitly mentions the item to be sold, including its price and quality, to the buyer, while simultaneously establishing a certain amount of profit. Meanwhile, in the case of certain traditional markets, particularly in the sale of mixed rice, neither the seller nor the buyer specifies the process of mixing the rice, thus resulting in rice with various quality variations. This study aims to delve into the practice of buying and selling mixed rice from the perspective of Islamic Law in Traditional Markets. The research method employed is descriptive qualitative research with the application of analytical techniques based on an inductive approach. Based on the research findings, it can be inferred that the Islamic legal scrutiny of the practice of selling mixed rice in traditional markets involves various types of rice variations based on their quality. The quality of the rice is determined by the extent to which high-quality rice is mixed with low-quality rice. According to the perspective of Islamic Law, the transaction of buying and selling mixed rice is deemed prohibited (haram) as it is considered to involve deceptive elements that can harm one of the parties. This deceitful practice, which could encompass misrepresentation (tadlis) and uncertainty (gharar) regarding the quality in the transaction of buying and selling mixed rice, is deemed detrimental to the general public. Therefore, the marketing of mixed rice falls under the category of rice marketing that is prohibited according to the principles of Sharia.